The link between childhood physical activity enjoyment and adult kinesiophobia in individuals with chronic low back pain - Haowei Liu; Hansen Li; Li Huang; Haodong Tian; Jinlong Wu; Qinwen Guan; Zhenhuan Wang; Xing Zhang; Zhou Yang; Li Peng (BMC Public Health, 2024)
Abstract Background This study aimed to investigate the relationship between childhood physical activity enjoyment and current kinesiophobia among individuals with chronic low back pain (CLBP), considering the mediating influence of adult physical activity. Methods We recruited 648 adults (474 males, 174 females) with CLBP through an online platform. Of these, 99.1% (n = 642) were aged 18–60 years, and 0.9% (n = 6) were older than 60 years. Childhood physical activity enjoyment was retrospectively assessed using a single-item question to gauge participants’ enjoyment during primary school. Kinesiophobia was measured with the 11-item Tampa Scale for Kinesiophobia (TSK-11), and physical activity was assessed focusing on walking, moderate, and vigorous physical activities. Age, sex, education, and income served as control variables in the analysis. Results A significant negative association was found between childhood physical activity enjoyment and adult kinesiophobia. Additionally, childhood physical activity enjoyment was positively associated with adult physical activity across the three types of physical activities. In the adjusted mediation model, walking was identified as the only statistically significant partial mediator. Conclusion The findings highlight the long-term protective role of childhood physical activity enjoyment against the development of kinesiophobia in adulthood. Walking, in particular, holds unique therapeutic potential, emphasizing the importance of fostering physical activity enjoyment early in life for sustained physical activity and reduced risk of kinesiophobia among CLBP patients.